Pengaruh Perbandingan Tepung Ubi Jalar Ungu (Ipomoea batatas L.) dan Terigu terhadap Karakteristik Cilok - Kurniawan, Andreas; Sri Wiadnyani, Anak Agung Istri; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p16, 2023)
The purpose of this study was to find the effect of purple sweet potato flour ( Ipomoea batatas L.) and wheat  flour ratio to produce cilok with the best characteristics. This study used a Completely Randomized Design  with 5 levels of purple sweet potato flour and wheat flour ratio, namely 0%:100%, 10%:90%, 20%:80%,  30%:70%, and 40%:60%. The treatment was repeated 3 times to obtain 15 experimental units. Parameters  observed were water content, ash content, protein content, fat content, carbohydrate content, crude fiber  content, antioxidant activity, hedonic test for color, aroma, texture, taste, overall acceptance and scoring  test for color, texture and taste. The data were analyzed by analysis of variance and if the treatment had a  significant effect, it was followed with the Duncan Multiple Range Test (DMRT). The result showed that  purple sweet potato flour and wheat flour ratio had a significant effect on water content, protein content,  fat content, carbohydrate content, crude fiber content, antioxidant activity, hedonic test on color and scoring  test (color and taste). The ratio of 40% purple sweet potato flour and 60% wheat flour produced the best  cilok characteristics with water content 48.44%, ash content 1.4%, protein content 2.85%, fat content  1.02%, carbohydrate content 46.3%, crude fiber content 3.81%, 74.41% antioxidant activity, also the  sensory characteristics were dark purple and slightly liked, the aroma was slightly liked, the texture was  slightly chewy and slightly liked, the taste was like purple sweet potato and slightly liked, and the overall  acceptance was slightly liked.